LABEL” KUTU LONCAT” DI TEMPAT KERJA, EKSPLORASI WORK LIFE BALANCE SEBAGAI PREFERENSI PEKERJAAN PADA GENERASIMILENIA DAN ZILENIA - Imanda Nabilasasi; Reza Fitriani; Raisya Amalia; Muhammad Yusuf (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
This study aims to determine the effect of Self-Efficacy, Emotional Intelligence, and Work Attitude on Work-Life Balance of Millennial and Zilenia Generation Employees. The approach used in the study is an associative approach. The population in the study amounted to 120 employees with a sample of 120 millennial generation employees. Data collection techniques used were observation, questionnaires, and literature studies. Data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, T tests, and F tests processed using the Statistical Product and Service Solution (SPSS) program. The results of the study show that Self-Efficacy (X1) has a significant effect on Work-Life Balance. Emotional Intelligence (X2) has an effect on Work-Life Balance. Work Attitude Affects Work-Life Balance and Self-Efficacy (X1). Emotional Intelligence (X2) and Work Attitude simultaneously (simultaneously) affect Work-Life Balance of Millennial and Zilenia Generation Employees.